Noncompliance with the national vaccination scheme in children in the peruvian jungle, year 2019: No cumplimiento del esquema nacional de vacunación en niños de la selva peruana, año 2019 - Kaway Caceda, Luis T. (2022)
In the past decade, levels of coverage on children vaccination had been decreasing nationwide, even more in the Peruvian jungle, reason why is an important public health’s subject to attend. The purpose of this investigation was to analyze maternal and social factors that are associated with incomplete vaccination schedules on children under 5 years old on the Peruvian jungle. It is an observational, analytic investigation, using a secondary source from the Demographic and Family survey (ENDES) from 2019, where is found the information of all the under 5 years old with the healthcare card of oral information given by the mother. Then after selecting the chosen variables, we used the SPSS statistic program for the posterior analysis. Of the 4373 surveys studied; it was shown that 57.5% of children under 5 years have the incomplete vaccination schedule. The multivariate analysis found that non-compliance with the vaccination schedule associated with maternal and social factors such as not having health insurance (ORa 1.72; p<0.01, IC95% 1.39-2,13), poverty (ORa-1,427, p<0.01, IC95% 1.89-1.71), native mother tongue (ORa-1.50, p<0.01, IC-1.13-2,0), problems attending the health center (ORa-1,213, p=0.02, IC95% 1.02-1.44), live outside the city (ORa-1.31, p<0.01, IC95% 1.09- 1.58), age under the age of 24 as a mother/guardian (ORa-1.38, p<0.01, IC95% 1,186-1,619). Not having health insurance, living in poverty, having trouble going to the health center, living outside the city, having a different mother tongue than Spanish and age under 24 are factors associated with non-compliance with the vaccination schedule.